2021
DOI: 10.1186/s12935-021-02134-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism underlying the apoptotic modulation by ethanol extract of Pseudolarix kaempferi in mucoepidermoid carcinoma of the salivary glands

Abstract: Background Pseudolarix kaempferi is a traditional Chinese natural product that possesses the potential cytotoxic effects against cancer. However, the precise molecular mechanism underlying its cytotoxic effects has not yet been completely elucidated. Here, we clarify the mechanism via which the ethanol extract of P. kaempferi (EEPK) leads to cytotoxicity mediated by apoptosis in mucoepidermoid carcinoma (MEC) originating from the salivary glands. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Mcl-1 mRNA levels were unchanged following PPT treatment, which ruled out the possibility that PPT affected the transcriptional regulation of Mcl-1. Numerous studies have demonstrated that decreased Mcl-1 expression, which may be caused by various compounds in cancer cells, is dependent on proteasomal processes ( 23 , 51 ). Thus, it is hypothesized that PPT induces a rapid turnover of Mcl-1 protein in OSCC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Mcl-1 mRNA levels were unchanged following PPT treatment, which ruled out the possibility that PPT affected the transcriptional regulation of Mcl-1. Numerous studies have demonstrated that decreased Mcl-1 expression, which may be caused by various compounds in cancer cells, is dependent on proteasomal processes ( 23 , 51 ). Thus, it is hypothesized that PPT induces a rapid turnover of Mcl-1 protein in OSCC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…These two apoptotic pathways eventually converge toward the formation of cleaved caspase-3 and, finally, cleaved PARP, followed by cell demise (20). Several natural products exert tumor-inhibitory activities by stimulating the intrinsic and extrinsic apoptotic signaling pathways exclusively, respectively, or by triggering the two pathways simultaneously (36)(37)(38). In the latter cellular context, the intrinsic and extrinsic apoptotic pathways can be integrated through the truncation of the BH3 interacting domain death agonist (Bid) protein, which is a process that is facilitated by c-caspase-8 (39).…”
Section: Discussionmentioning
confidence: 99%